SOC solutions of male survivors of childhood sexual abuse: an exploratory collective case study - Spiehs, Justin (Kansas State University, 2018)
This exploratory collective case study utilized structured interviews to investigate retrospective reports of potential losses in resources resulting from childhood sexual abuse (CSA) and whether Selection, Optimization, and Compensation (SOC) “Solutions” were used by six adult male survivors to help offset these losses. Within- and between-case analyses of thematic reports are offered. Specifically, a description of each case is presented with an overview of the analysis of both unique and shared SOC Solution responses. SOC is presented in developmental research literature as a model of self-regulation across the life span. Retrospective reports of the participants suggest they did not engage in self-regulation in response to this childhood trauma. Rather, their reports evidenced the use of reactive “holding strategies” as opposed to deliberate use of selection strategies. This suggestive discovery supports previous research indicating that child survivors of trauma may have reduced self-regulation capacities. Childhood self-regulation may occur through the support of an adult (“dyadic regulation”). Findings further illustrate that the abuse may increase isolation in childhood. However, isolation, as an immediate childhood response to the abuse, may have reduced their potential for dyadic regulation as they dealt with the abuse on their own. Participants reports indicated the use” holding strategies” in childhood that were typically maladaptive. This may have led to the use of maladaptive optimization solutions in childhood that supported these holding strategies. Participants’ reports indicate that they were unable to deliberately access and implement adaptive compensation solutions until they reached adulthood, where these solutions seemed to contribute to more effective loss-directed responses. Baseline reserve capacity and developmental reserve capacity related to adaptive responding in the SOC model are discussed in the present context of trauma. The contributions of this case study to theory building in both the SOC developmental literature and clinical practice with male survivors of CSA are cautiously offered. Results may inform the theoretical reach of the SOC model, showing the limits of the self-regulation model when applied to childhood trauma. The study may inform clinical practice with this population by highlighting the importance of helping children self-regulate through dyadic regulation. Through this process, children may be guided by supportive adults to intentionally select adaptive goals to focus on following sexual abuse. Resources that male survivors may access and/or develop to adjust to the losses caused by childhood sexual abuse are offered.
Keywords: selection; optimization; compensation model; male survivors of childhood sexual abuse